The Internal Geography of Trade : Lagging Regions and Global Markets - Farole, Thomas (Washington, DC: World Bank, 2013)
Economic theory, including endogenous growth, the role of institutions, and, most importantly, the New Economic Geography (NEG), have made significant progress in explaining the emergence of core-periphery patterns behind this divergence. They point to the critical role of agglomeration, which confers benefits to metropolitan cores that have the advantages of large markets, deep labor pools, links to international markets, and clusters of diverse suppliers and institutions. Regions relatively near the metropolitan core are likely to benefit from spillovers and congestion-related dispersion. Regions further outside the core however, are not only less able to take advantage of spillovers, but also more likely to be far removed from key infrastructural, institutional, and interpersonal links to regional and international markets. As a result, they face significant challenges to becoming competitive locations to host economic activity. Thus the geographical pattern of core and peripheral regions is increasingly manifest in an economic pattern of 'leading' and 'lagging' regions